Comparative analysis of lipid accumulation and fatty acid composition in microalgae chaetoceros sp. and isochrysis sp. under varied light intensities for biodiesel production / Zamzila Erdawati Zainol ... [et al.] - Zainol, Zamzila Erdawati; Ahmad, Aziani; Kamaruddin, Sharir Aizat; Abd. Aziz, Khairul Naim (Faculty of Applied Sciences, 2024)
The escalating demand for renewable and sustainable energy sources has spurred research into innovative alternatives to conventional fossil fuels. Among these alternatives, microalgae have emerged as promising for biodiesel production due to their rapid growth rates, high lipid content, and ability to thrive in diverse environmental conditions. However, the efficient conversion of microalgae biomass into biodiesel hinges on optimizing lipid accumulation and ensuring desirable fatty acid compositions. Therefore, this study investigates the effects of different light intensities on lipid accumulation and fatty acid composition in two prevalent microalgae species, Chaetoceros sp. and Isochrysis sp., to optimize their biodiesel potential in seawater containing sodium metasilicate and Conway medium. The cultivation was carried out at three different light intensities (1000 lux, 2000 lux, and 3000 lux) with a photoperiod of 12:12 hours of light: dark cycle. The results showed that the samples achieved peak growth rates at a light intensity of 2000 lux, with Chaetoceros sp. reaching 12.32% growth and Isochrysis sp. achieving 9.72%. Chaetoceros sp. and Isochrysis sp. displayed their peak saturated fatty acid content, crucial for high-grade biodiesel, at the 2000 lux light intensity. Chaetoceros sp. reached 51.06%, while Isochrysis sp. recorded 44.05%. Additionally, both species contained notable proportions of C14, C16, and C18 fatty acids, essential components in selecting viable alternative biodiesel sources. Therefore, a light intensity of 2000 lux is recommended to be applied during the growing stage of this seaweed to produce quality biodiesel.